Mister Rogers and me [videorecording (DVD)] - Wagner, Benjamin; Wagner, Christofer; Rogers, Fred; Russert, Tim, 1950-2008; Stamberg, Susan, 1938-; Brown, Marc Tolon (PBS Distribution, 2012)
Mister Rogers summered in a modest house on a quiet corner of Nantucket Island. MTV producer Benjamin Wagner's mother rented the cottage next door. Mister Rogers really was his neighbor. On the afternoon of their first meeting, America's Favorite Neighbor asked the young journalist about his job. Wagner expressed enthusiasm tempered with an iota of ambivalence. After Rogers' death in 2003, Wagner and his brother, Christofer, set out to learn more about the man himself.